THE INFLUENCE OF ECONOMIC GLOBALIZATION ON LEGAL POLICY IN THE PERSPECTIVE OF PEOPLE’S ECONOMY: THE INFLUENCE OF ECONOMIC GLOBALIZATION ON LEGAL POLICY IN THE PERSPECTIVE OF PEOPLE’S ECONOMY - Wati, Erna; Endi, Ignasius Novie; Priambada, Bintara Sura; Sarsiti, Sarsiti; Trisnowati, Juni (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
Economic globalization has a significant impact on legal policy in Indonesia. Free trade and increased international investment demand adjustments and harmonization of national laws to be competitive and protect national interests. The current global economic impact faces increasing uncertainty. Several factors are driving this, the most significant of which are geopolitical conflicts between several countries, escalating trade wars, declining economic growth prospects in many countries, and global inflation. The global economy refers to the entire world economic system, which involves interactions and interdependence between various countries through trade, investment, and capital flows. Therefore, Indonesia can capitalize on the opportunities of globalization to achieve sustainable and inclusive economic growth, while minimizing its negative impacts, by upholding the constitutional mandate of a people-oriented economy with active community participation.